2016
DOI: 10.1080/07347332.2016.1265624
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors as activated patients: Exploring the relationship between cancer history and patient activation

Abstract: Many cancer survivors experience long-term physical and psychosocial sequalae. As such, there is a need for survivors to be activated and participate in their own health care. Our study explores the relationship between cancer history and patient activation. We used data from the 2013 Health Information National Trends Survey (N = 3185, response rate = 35.19%). Survivors had approximately 70% higher odds of being highly activated compared to those with no cancer history. Level of activation did not vary across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Although we did not observe differences among smokers versus non-smokers with respect to searching for health information online, our findings are consistent with prior studies that have reported widespread use of the internet among smokers [ 35 , 39 ]. Consistent with prior studies, we observed increased HRIU among individuals with a personal or family history of cancer, compared to those without [ 36 , 37 , 38 , 68 , 69 ]. These findings highlight the potential for eHealth and mHealth-based interventions to target the unique needs of cancer survivors [ 36 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although we did not observe differences among smokers versus non-smokers with respect to searching for health information online, our findings are consistent with prior studies that have reported widespread use of the internet among smokers [ 35 , 39 ]. Consistent with prior studies, we observed increased HRIU among individuals with a personal or family history of cancer, compared to those without [ 36 , 37 , 38 , 68 , 69 ]. These findings highlight the potential for eHealth and mHealth-based interventions to target the unique needs of cancer survivors [ 36 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…This is a thirteen‐item instrument that measures knowledge, skills and confidence to self‐manage. It has been widely used internationally to measure self‐management in people living with cancer 37–39 …”
Section: Methodsmentioning
confidence: 99%
“…It has been widely used internationally to measure self-management in people living with cancer. [37][38][39] Based on the responses to the 13 items each participant receives a PAM-13 score that can range from 0 to 100 with higher scores indicative of higher activation. The individual PAM-13 scores can be categorised into one of four levels of activation which represent a developmental progression from being passive with regard to one's health to being highly proactive about self-management.…”
Section: Self-managementmentioning
confidence: 99%
“…Females (aged 18 years or over) newly diagnosed with early stage breast cancer as a first primary diagnosis will be eligible to take part. Eligibility was restricted to early stage and first primary diagnoses as metastatic patients may have confounding care and psychosocial experiences and patient activation naturally increases with time after a breast cancer diagnosis [22]. Patients must complete the baseline measure before starting anticancer treatment.…”
Section: Participantsmentioning
confidence: 99%